2017
DOI: 10.1155/2017/4517469
|View full text |Cite
|
Sign up to set email alerts
|

Cold Storage of Two Selections of Soursop (Annona muricataL.) in Nayarit, Mexico

Abstract: The maturity of two selections of soursop (G1 and G2) from Nayarit, Mexico, was evaluated under environmental conditions at 22°C and refrigeration at 15°C stored for 6 and 8 days, respectively. Maximum CO2and ethylene values were present on the fifth and sixth day. The fruits exposed at 15°C had a significantly lower weight loss (5%) and showed no chilling injury. The firmness of two selections decreased more than 90%. The concentration of TSS increased to 5.3 to 15°Brix, and the titratable acidity was higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…e decrease in the concentration of the phenols could be influenced by the oxidation of these compounds and by the activity of the enzyme polyphenol oxidase and peroxidase [53,58]. An investigation conducted by Jiménez-Zurita et al [30], in soursop fruits stored at 22°C, reported 74.20 mg EAG/ 100 gFW, whose values are similar to those found in the present investigation. Silva and Sirasa [59] reported 86.5 mg EAG/100 gFW in fruits of Annona muricata L. and 199.1 mg EAG/100 gFW in the pulp of Annona reticulata fruits from Sri Lanka.…”
Section: Total Phenolic Content (Tpc)supporting
confidence: 89%
See 4 more Smart Citations
“…e decrease in the concentration of the phenols could be influenced by the oxidation of these compounds and by the activity of the enzyme polyphenol oxidase and peroxidase [53,58]. An investigation conducted by Jiménez-Zurita et al [30], in soursop fruits stored at 22°C, reported 74.20 mg EAG/ 100 gFW, whose values are similar to those found in the present investigation. Silva and Sirasa [59] reported 86.5 mg EAG/100 gFW in fruits of Annona muricata L. and 199.1 mg EAG/100 gFW in the pulp of Annona reticulata fruits from Sri Lanka.…”
Section: Total Phenolic Content (Tpc)supporting
confidence: 89%
“…Tovar-Gómez et al [29] reported losses around 2.56 and 2.46% in soursop fruits coated with wax emulsions and 1-MCP in soursop fruits stored under similar conditions to those used in this investigation. Jiménez-Zurita et al [30], in uncoated soursop fruits stored for seven days (four days at 15°C and then three days at 22°C), reported cumulative weight losses of 2.3% and 2.7%, respectively. ese same authors reported a daily mass loss between 1.34 and 1.41% in uncoated soursop fruits stored for six days at 22°C, presenting accumulated mass losses of 6.7 and 7.1%.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations